Intelligent Systems and Applications Extended and Selected Results from the SAI Intelligent Systems Conference (IntelliSys) 2015 - Bi, Yaxin; Kapoor, Supriya; Bhatia, Rahul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is a remarkable collection of chapters covering a wider range of topics, including unsupervised text mining, anomaly and Intrusion Detection, Self-reconfiguring Robotics, application of Fuzzy Logic to development aid, Design and Optimization, Context-Aware Reasoning, DNA Sequence Assembly and Multilayer Perceptron Networks. The twenty-one chapters present extended results from the SAI Intelligent Systems Conference (IntelliSys) 2015 and have been selected based on high recommendations during IntelliSys 2015 review process. This book presents innovative research and development carried out presently in fields of knowledge representation and reasoning, machine learning, and particularly in intelligent systems in a more broad sense. It provides state - of - the - art intelligent methods and techniques for solving real world problems along with a vision of the future research.
A Hybrid Intelligent Approach for Metal-Loss Defect Depth Prediction in Oil and Gas Pipelines -- Predicting Financial Time Series Data Using Hybrid Model -- Diagnosis System for Predicting Bladder Cancer Recurrence using Association Rules and Decision Trees -- An Unsupervised Text-Mining Approach and a Hybrid Methodology to Improve Early Warnings in Construction Project Management -- Quantitative Assessment of Anomaly Detection Algorithms in Annotated Datasets from the Maritime Domain -- Using Fuzzy PROMETHEE to Select Countries for Developmental Aid -- Self-Reconfiguring Robotic Framework Using Fuzzy and Ontological Decision Making -- Design and Optimization of Permanent Magnet Based Adhesion Module for Robots Climbing on Reinforced Concrete Surfaces -- Implementation of PID, Bang-bang and Backstepping con-trollers on 3D Printed Ambidextrous Robot Hand -- Multiple Robots Task Allocation for Cleaning and Delivery -- Optimal Tuning of Multivariable Centralized Fractional Order PID Controller using Bat Optimization and Harmony Search Algorithms for Two Interacting Conical Tank Process -- Entity Configuration and Context-Aware reasoNer (CAN) towards Enabling an Internet of Things Controller -- Track-Based Forecasting of Pedestrian Behavior by Polynomial Approximation and Multilayer Perceptrons -- Assembly Assisted by Augmented Reality (A3R) -- Maximising Overlap Score in DNA Sequence Assembly Problem by Stochastic Diffusion Search -- A Comparative Analysis of Detecting Symmetries in Toroidal Topology -- Power Quality Enhancement in Off-Grid Hybrid Renewable Energy Systems Using Type-2 Fuzzy Control of Shunt Active Filter -- Fast Intra Mode Decision for HEVC -- WSN Efficient Data Management and Intelligent Communication for Load Balancing Based on Khalimsky Topology and Mobile Agents -- Indirect Method of Learning Weights Parameters of Intuitionistic Statement Networks -- CombinedData and Execution Flow Host Intrusion Detection using Machine Learning.
Keywords: Computational intelligence; Artificial intelligence; System theory; Mathematical physics; Computational Intelligence; Artificial Intelligence; Complex Systems; Theoretical, Mathematical and Computational Physics